Sociocultural, economic and ethnic homogeneity in residential mobility and spatial sorting among couples. (June 2019) - van Gent, Wouter; Das, Marjolijn; Musterd, Sako
This study aims to advance the spatial conceptualization of 'social homophily' by relating the match, or mismatch, between a household's social and sociocultural characteristics and the characteristics of the neighbourhood of residence to the probability of moving away from that neighbourhood. Three matching dimensions were investigated: economic status, ethnic background and sociocultural disposition. This paper's focus is on the sociocultural dimension because this has not been included extensively in large-scale research so far. Initially we investigate how level of education at the household level interacts with education composition at the neighbourhood level. To further investigate the sociocultural dimension, we then include the share of each partner's income in the total household income in our analyses. Based on the spatial literature at the intersections of class, gender and family, we assume that, together with higher education, the intra-household distribution of income reflects a broader set of sociocultural values. We make use of large- N register data to analyse the residential and mobility behaviour of all registered stable couples in the four largest Dutch urban regions between 2008 and 2009. Our analyses indicate that the degree to which a household 'matches' its social surroundings negatively affects its probability of leaving. This is the case for all three dimensions, with sociocultural disposition having the largest effect. The conclusion reflects on the importance of these findings for social homophily, sorting and residential segregation, and proposes directions for further research.